Iron necessity: the secret of Wolbachia's success? - Alessandra Christina Gill; Alistair C Darby; Benjamin L Makepeace (Public Library of Science (PLoS), 2014)
The bacterium Wolbachia (order Rickettsiales) is probably the world's most successful vertically-transmitted symbiont, distributed among a staggering 40% of terrestrial arthropod species. Wolbachia has great potential in vector control due to its ability to manipulate its hosts' reproduction and to impede the replication and dissemination of arboviruses and other pathogens within haematophagous arthropods. In addition, the unexpected presence of Wolbachia in filarial nematodes of medical and veterinary importance has provided an opportunity to target the adult worms of Wuchereria bancrofti, Onchocerca volvulus, and Dirofilaria immitis with safe drugs such as doxycycline. A striking feature of Wolbachia is its phenotypic plasticity between (and sometimes within) hosts, which may be underpinned by its ability to integrate itself into several key processes within eukaryotic cells: oxidative stress, autophagy, and apoptosis. Importantly, despite significant differences in the genomes of arthropod and filarial Wolbachia strains, these nexuses appear to lie on a continuum in different hosts. Here, we consider how iron metabolism may represent a fundamental aspect of host homeostasis that is impacted by Wolbachia infection, connecting disparate pathways ranging from the provision of haem and ATP to programmed cell death, aging, and the recycling of intracellular resources. Depending on how Wolbachia and host cells interact across networks that depend on iron, the gradient between parasitism and mutualism may shift dynamically in some systems, or alternatively, stabilise on one or the other end of the spectrum.